Dampak Kesenjangan Akses Pendidikan dan Faktor Ekonomi Keluarga terhadap Mobilitas Sosial - Edo, Abdulloh; Yasin, Muhammad (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
Education is a key factor in encouraging social mobility in Indonesia. However, unequal access to quality education, especially in rural areas, creates significant gaps in opportunities to improve social status. This research aims to analyze the impact of gaps in educational access and family economic factors on social mobility in South Sangatta. Using a qualitative descriptive approach, data was collected through observation and in-depth interviews with various relevant informants. The research results show that limited access to adequate education in South Sangatta has a direct impact on the low level of social mobility. Children from well-off families have greater opportunities to obtain quality education compared to children from less well-off families. Family economic factors are proven to be the main determinant in the effectiveness of education as a tool for increasing social mobility. This research highlights the need for equitable access to education and economic interventions to increase social mobility in rural areas such as South Sangatta.